2003
DOI: 10.1038/sj.mp.4001255
|View full text |Cite
|
Sign up to set email alerts
|

Depressive-like behavior and stress reactivity are independent traits in a Wistar Kyoto × Fisher 344 cross

Abstract: Depression is a heritable disorder that is often precipitated by stress. Abnormalities of the stress-reactive hypothalamic-pituitary-adrenal (HPA) axis are also common in depressed patients. In animal models, the forced swim test (FST) is the most frequently used test of depressive-like behavior. We have used a proposed animal model of depression, the Wistar Kyoto (WKY) rat, to investigate the relationship as well as the mode of inheritance of FST behaviors and HPA measures. Through reciprocal breeding of WKY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 75 publications
(88 reference statements)
7
43
0
Order By: Relevance
“…Further, WLI males had a higher plasma CORT response to restraint stress than WMI males, in agreement with our previous findings that 'normal' F344 males have a higher plasma CORT response to the same restraint stress than 'depressed' WKY males. 25 Although elevated HPA activity has been thought to be associated with depression, recent reports have found no such correlation in animal models. 25,32 Further, it has been reported that depressed patient subtypes can show either increased or decreased HPA activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, WLI males had a higher plasma CORT response to restraint stress than WMI males, in agreement with our previous findings that 'normal' F344 males have a higher plasma CORT response to the same restraint stress than 'depressed' WKY males. 25 Although elevated HPA activity has been thought to be associated with depression, recent reports have found no such correlation in animal models. 25,32 Further, it has been reported that depressed patient subtypes can show either increased or decreased HPA activity.…”
Section: Discussionmentioning
confidence: 99%
“…25 Although elevated HPA activity has been thought to be associated with depression, recent reports have found no such correlation in animal models. 25,32 Further, it has been reported that depressed patient subtypes can show either increased or decreased HPA activity. 33 Several other rat lines have been selectively bred based on behavioral paradigms, usually starting with outbred populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FST procedure used was described previously. 45 Briefly, animals were placed into a glass cylinder (30 cm diameter, 45 cm deep) of 251C tap water for 15 min. After 24 h, rats were again placed into the cylinder of water for 5 min.…”
Section: Forced Swim Testmentioning
confidence: 99%
“…All testing took place between 1100 and 1500 h. Activity during the second swim test was video-recorded for subsequent scoring using a time-sampling technique previously described 46 in which behavior was scored as immobility, climbing, or swimming every 5 s. We have previously shown that immobility in the FST is not related to body weight. 45 Morris water maze At 80-90 days of age, minimum 20 days after the FST, the hidden platform version of the Morris water maze (MWM) was used to assess spatial learning. We chose not to administer a 'visual cue' version of the water maze for the following reasons.…”
Section: Forced Swim Testmentioning
confidence: 99%